2017
DOI: 10.2147/ceor.s146280
|View full text |Cite
|
Sign up to set email alerts
|

The cost of successful antiviral therapy in hepatitis C patients: a comparison of IFN-free versus IFN-based regimens at an individual patient level in Australia

Abstract: BackgroundChronic hepatitis C remains a major global health burden with serious long-term consequences if left untreated. Recently the treatment standard of care has shifted to new interferon (IFN)-free drug regimens, which have been shown to be safe and effective. The aim of our study was to assess and compare medical resource utilization and costs of successfully treating patients with IFN-based and IFN-free therapies in Australia.MethodsWe performed a retrospective chart review of 30 HCV-infected patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(31 reference statements)
2
1
0
Order By: Relevance
“…When the cost of the sofosbuvir/velpatasvir drug is reduced by 10, 20, and 50% from the current price of USD480 per treatment, the cumulative savings over the 5 years between scenarios A and B were estimated to be USD 1.6, 2, and 3 million, respectively. This study found that DAA drug was the key cost driver across all disease stages, ranging from 46 to 80% of the cost, which is consistent with findings from previous studies (4,21,23). Similarly, in the era of interferon-based treatment, HCV drug cost was also found to be the main driver of high treatment cost (4,22).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When the cost of the sofosbuvir/velpatasvir drug is reduced by 10, 20, and 50% from the current price of USD480 per treatment, the cumulative savings over the 5 years between scenarios A and B were estimated to be USD 1.6, 2, and 3 million, respectively. This study found that DAA drug was the key cost driver across all disease stages, ranging from 46 to 80% of the cost, which is consistent with findings from previous studies (4,21,23). Similarly, in the era of interferon-based treatment, HCV drug cost was also found to be the main driver of high treatment cost (4,22).…”
Section: Discussionsupporting
confidence: 90%
“…This study found that DAA drug was the key cost driver across all disease stages, ranging from 46 to 80% of the cost, which is consistent with findings from previous studies (4,21,23). Similarly, in the era of interferon-based treatment, HCV drug cost was also found to be the main driver of high treatment cost (4,22). The higher cost of HCV treatment with interferon-based drugs was related to the need for multiple courses of therapy and extended treatment duration (4) due to the low efficacy and higher failure rates of interferon.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation